EVALUASI EMERGY PENGEMBANGAN SISTEM BUDIDAYA UDANG SUPRA INTENSIF DI KAWASAN PESISIR MAMBORO, KOTA PALU, PROVINSI SULAWESI TENGAH - Vicky Rizky Katili; Luky Adrianto; Yonvitner yonvitner (Graduate School Bogor Agricultural University (SPs IPB), 2017)
Indonesia should pay greater attention on aquaculture due to a continous decrease in capture fisheries production. Shrimp is an excellent fishery commodity consumption in the global market, but the availability of supply is not yet fulfilled. The supra intensive aquaculture system has believed as a solution method for shrimp production. This study was trying to analyze the energy and emergy flow inside the supra intensive aquaculture system. Further analysis was done with emergy indices calculation to predict the future application of supra intensive system. The result of study shows the energy required in shrimp harvested from supra intensive system (transformity) was 1,12E+10 sej/g shrimps. This number represents it is needed more energy to produce per gram shrimps in supra intensive system compared to conventional shrimp pond in Ecuador and in Brazil. System more likely depend on purchased input which was indicated by very high EIR and ELR but in contrary relatively low EYR. Supra intensive aquaculture systems tend to be unsustainable in the long term by the very low value of ESI.